Russian Society of Cardiology position paper on 2018 Guidelines of the European Society of Cardiology/European Society of Arterial Hypertension for the management of arterial hypertension - Zh. D. Kobalava; A. O. Konradi; S. V. Nedogoda; G. P. Arutyunov; E. I. Baranova; O. L. Barbarash; S. V. Villevalde; A. S. Galyavich; M. G. Glezer; O. M. Drapkina; Yu. V. Kotovskaya; R. A. Libis; et al. (Российский кардиологический журнал, 2018)
.